Aplicação para localização e gerenciamento de serviços domésticos para autônomos - Vieira, Elias Ricardo (2019)
Some people who lack financial, space, time or availability conditions to have the necessary equipment to wash clothes and shoes. However, there are people who have these equipment and time available to do such services. With this in mind, in this work a web system was developed to find out who needs these services, providing a way so that the client can, in a way that is more comfortable to him, to solve the situation and not need to acquire an equipment, besides to enable the service provider to earn an extra income through previously idle equipment.